The effect of perceived usefulness, perceived ease of use, trust, enjoyment and perceived security on intention to use e-wallet on SME customers - Fadira Zena Amanda; Perengki Susanto; Rahmiati Rahmiati (Jurnal Kajian Manajemen dan Wirausaha, 2022)
This study aims to determine the effect of Perceived Usefulness, Perceived Ease of Use, Trust, Enjoyment and Perceived Security on Intention to Use E-Wallet on SME customers in Padang City. The population in this study are SME customers in the city of Padang. The number of samples in this study were 260 respondents. The data in this study were collected through online questionnaires and data processing was carried out using Structural Equation Modeling (SEM) using SmartPLS software. The results of this study indicate that (1) Perceived Usefulness has a positive and significant effect on Intention to use on E-wallet. (2) Perceived Ease of Use has a positive and insignificant effect on Intention to Use on E-wallet. (3) Perceived Ease of Use has a positive and significant effect on Perceived Usefulness. (4) Enjoyment has a positive effect on Intention to Use. (5) Enjoyment has a positive and significant effect on Trust. (6) Trust has a positive and insignificant effect on Intention to Use. (7) Perceived Security has a positive and insignificant effect on Intention to Use. (8) Perceived Security has a positive effect on Trust.